Orphan optical flare as SOSS emission afterglow, localization in time. Issue 4 (27th September 2022) - Lipunov, V; Kornilov, V; Zhirkov, K; Tyurina, N; Gorbovskoy, E; Vlasenko, D; Simakov, S; Topolev, V; Francile, C; Podesta, R; Podesta, F; Svinkin, D; et al.
ABSTRACT: We report on MASTER optical observations of an afterglow-like optical and X-ray transient AT2021lfa/ZTF21aayokph. We detected the initial steady brightening of the transient at 7σ confidence level. This allowed us to use smooth optical self-similar emission of GRBs model to constrain the explosion time to better than 14 min as well as to estimate its initial Lorentz factor Γ0 = 20 ± 10. Taking into consideration the low Γ0 and non-detection in gamma-rays, we classify this transient as the first failed GRB afterglow.